Piezoelectrically modulated touch pressure sensor using a graphene barristor. (18th February 2019) - Hwang, Hyeon Jun; Kim, So-Young; Kang, Soo Cheol; Allouche, Billal; Yang, Jin Ho; Lee, Byoung Hun
Abstract: A touch pressure sensor using a graphene-Si Schottky junction barristor gated with the piezoelectric polymer poly(vinylidenefluoride-co-trifluoroethylene) has been demonstrated that combines a high on–off ratio (over 10 2 ) and low leakage current characteristics. The performance of this device was optimized by presetting the initial Fermi level of graphene using a polymer doping process. Sensing current modulation ratios up to 312% were achieved under 3 MPa touch pressure.